A set of rational numbers 2 (correct version)

Calculus Level 3

Lets say you have two natural numbers x x and n n with n 1 n\neq 1 .

Lets say you also have a set with all multiples of n n until x n x \cdot n :

M = { 1 n ; 2 n ; 3 n ; ; x n } M=\left\{ 1\cdot n;2\cdot n;3\cdot n;\cdots ;x\cdot n \right\}

Lets say you have another set with the powers of n n until n x { n }^{ x } :

N = { n 1 ; n 2 ; n 3 ; ; n x } N=\left\{ { n }^{ 1 };{ n }^{ 2 };{ n }^{ 3 };\cdots ;{ n }^{ x } \right\}

Now you store every possible fraction, where the numerator is an element of M M and the denominator is an element of N N in a third set Q Q . Q Q can hold multiple times the same value. For example, when n = 2 n=2 and x 2 x\ge 2 , Q Q holds 2 2 \frac { 2 }{ 2 } and 4 4 \frac { 4 }{ 4 } even both fractions have the same value.

Q ˉ \bar { Q } is the arithmetic mean of Q Q . f ( n ) = lim x Q ˉ f\left( n \right) =\lim _{ x\rightarrow \infty }{ \bar { Q } } . Which one is correct?

Here you can find the first problem.

For those, who wonder why I reuploaded this problem after a few minutes. There was a typing error in the correct solution.

f ( n ) = 1 n 1 f\left( n \right) =\frac { 1 }{ n-1 } f ( n ) = n 2 ( n 1 ) f\left( n \right) =\frac { n }{ 2\cdot \left( n-1 \right) } f ( n ) = 1 2 ( n 1 ) f\left( n \right) =\frac { 1 }{ 2\cdot \left( n-1 \right) } f ( n ) = 0 f\left( n \right) =0 not enought information f ( n ) = n n 1 f\left( n \right) =\frac { n }{ n-1 }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

CodeCrafter 1
May 12, 2019

From the first problem we know:

Q ˉ = ( i = 1 x n i ) ( j = 1 x 1 n j ) x 2 \bar { Q } =\frac { \left( \sum _{ i=1 }^{ x }{ n\cdot i } \right) \cdot \left( \sum _{ j=1 }^{ x }{ \frac { 1 }{ { n }^{ j } } } \right) }{ { x }^{ 2 } }

We also know that:

i = 1 x n i = n x ( x + 1 ) 2 \sum _{ i=1 }^{ x }{ n\cdot i } =n\cdot \frac { x\cdot \left( x+1 \right) }{ 2 }

j = 1 x 1 n j = n x 1 n x ( n 1 ) \sum _{ j=1 }^{ x }{ \frac { 1 }{ { n }^{ j } } } =\frac { { n }^{ x }-1 }{ { n }^{ x }\cdot \left( n-1 \right) }

Thus Q ˉ = n x ( x + 1 ) ( n x 1 ) 2 x 2 n x ( n 1 ) = x n x x + n x 1 2 x n x 1 ( n 1 ) = x n x 1 ( n 1 n x + n x 1 x n x 1 ) 2 x n x 1 ( n 1 ) = n 1 n x + n x 1 x n x 1 2 ( n 1 ) \bar { Q } =\frac { n\cdot x\cdot \left( x+1 \right) \cdot \left( { n }^{ x }-1 \right) }{ 2\cdot { x }^{ 2 }\cdot { n }^{ x }\cdot \left( n-1 \right) } =\frac { x\cdot { n }^{ x }-x+{ n }^{ x }-1 }{ 2\cdot x\cdot { n }^{ x-1 }\cdot \left( n-1 \right) } =\frac { x\cdot { n }^{ x-1 }\cdot \left( n-\frac { 1 }{ { n }^{ x } } +\frac { n }{ x } -\frac { 1 }{ x\cdot { n }^{ x-1 } } \right) }{ 2\cdot x\cdot { n }^{ x-1 }\cdot \left( n-1 \right) } =\frac { n-\frac { 1 }{ { n }^{ x } } +\frac { n }{ x } -\frac { 1 }{ x\cdot { n }^{ x-1 } } }{ 2\cdot \left( n-1 \right) }

And finally:

Q ˉ = lim x n 1 n x + n x 1 x n x 1 2 ( n 1 ) = n 2 ( n 1 ) \bar { Q } =\lim _{ x\rightarrow \infty }{ \frac { n-\frac { 1 }{ { n }^{ x } } +\frac { n }{ x } -\frac { 1 }{ x\cdot { n }^{ x-1 } } }{ 2\cdot \left( n-1 \right) } } =\boxed { \frac { n }{ 2\cdot \left( n-1 \right) } }

For those, who want a proof that j = 1 x 1 n j = n x 1 n x ( n 1 ) \sum _{ j=1 }^{ x }{ \frac { 1 }{ { n }^{ j } } } =\frac { { n }^{ x }-1 }{ { n }^{ x }\cdot \left( n-1 \right) } is true:

j = 1 x 1 n j = 1 n 1 + 1 n 2 + 1 n 3 + + 1 n x = m \sum _{ j=1 }^{ x }{ \frac { 1 }{ { n }^{ j } } } =\frac { 1 }{ { n }^{ 1 } } +\frac { 1 }{ { n }^{ 2 } } +\frac { 1 }{ { n }^{ 3 } } +\cdots +\frac { 1 }{ { n }^{ x } } =m

Then n m = 1 + 1 n 1 + 1 n 2 + 1 n 3 + + 1 n x 1 n\cdot m=1+\frac { 1 }{ { n }^{ 1 } } +\frac { 1 }{ { n }^{ 2 } } +\frac { 1 }{ { n }^{ 3 } } +\cdots +\frac { 1 }{ { n }^{ x-1 } } .

So: n m m = m ( n 1 ) = 1 + 1 n 1 + 1 n 2 + 1 n 3 + + 1 n x 1 ( 1 n 1 + 1 n 2 + 1 n 3 + + 1 n x ) = 1 1 n x n\cdot m-m=m\cdot \left( n-1 \right) =1+\frac { 1 }{ { n }^{ 1 } } +\frac { 1 }{ { n }^{ 2 } } +\frac { 1 }{ { n }^{ 3 } } +\cdots +\frac { 1 }{ { n }^{ x-1 } } -\left( \frac { 1 }{ { n }^{ 1 } } +\frac { 1 }{ { n }^{ 2 } } +\frac { 1 }{ { n }^{ 3 } } +\cdots +\frac { 1 }{ { n }^{ x } } \right) =1-\frac { 1 }{ { n }^{ x } }

and finally:

m = 1 n 1 1 n x ( n 1 ) = n x 1 n x ( n 1 ) m=\frac { 1 }{ n-1 } -\frac { 1 }{ { n }^{ x }\cdot \left( n-1 \right) } =\boxed { \frac { { n }^{ x }-1 }{ { n }^{ x }\cdot \left( n-1 \right) } }

CodeCrafter 1 - 2 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...